Unpreparedness in Self-Management: A Description of Self-Management of Type II Diabetes Mellitus Patients in Health Facilities - Femy Melia Rahmawati; Satriya Pranata; Yunie Armiyati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Type 2 diabetes mellitus is a metabolic disorder caused by hyperglycemia. If uncontrolled, it can be fatal. Therefore, effective self-management and self-control activities are necessary for sufferers. Self-management includes behaviors related to diet, exercise physique, monitoring sugar blood And maintenance foot. This study aims to identify self-management on patient DM type 2 in Internal Medicine Polyclinic, Sekarwangi Regional Hospital. This study used a quantitative descriptive method with a survey approach. The instrument used to measure diabetes self-management was the DSMQ (Diabetes Self-Management Questionnaire) questionnaire adapted into Indonesian. The sample size of this study was 120 type 2 DM patients, using a quota sampling method, in accordance with established inclusion and exclusion criteria. Data analysis used in this study was descriptive univariate analysis. This study shows that the characteristics of respondents were on average 53 years old, had suffered from DM for around 4 years, 61.6% were female, 44.1% had secondary education, 65% were married, 80.8% were employed, 73.3% had no family history of the disease, and 74.1% of respondents had never attended DM education . Analysis score s elf-management shared into three category that is Good Enough And bad, The results of this study showed that respondents who performed self-management were fair (42.5%), good (29.1%), and poor (28.3). The average subscales were fair glucose management, adequate dietary control, poor physical activity, and poor health services. This indicates that most respondents have not performed self-management effectively. It is important for nurses to facilitate proper self-management for DM patients and implement specific programs for DM patients.